2009
DOI: 10.1161/circheartfailure.108.814459
|View full text |Cite
|
Sign up to set email alerts
|

Large Animal Models of Heart Failure

Abstract: Abstract-Congestive heart failure (HF) is a clinical syndrome, with hallmarks of fatigue and dyspnea, that continues to be highly prevalent and morbid. Because of the growing burden of HF as the population ages, the need to develop new pharmacological treatments and therapeutic interventions is of paramount importance. Key Words: myocardial infarction Ⅲ myocardial remodeling Ⅲ overload states Ⅲ rapid pacing C ongestive heart failure (HF) is a constellation of symptoms, with hallmarks of fatigue and dyspnea, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(126 citation statements)
references
References 88 publications
1
125
0
Order By: Relevance
“…DCM is defined by structural hallmarks of left ventricle dilation and increased left ventricle chamber radius-to-wall thickness ratio, resulting in increased left ventricle wall stress (Dixon and Spinale 2009 HCM is a primary myocardial disease that has variable manifestations because the interactions between the many facets of systolic and diastolic dysfunction of the heart are complex (Lin et al 2002) (Kushwaha et al 1997). …”
Section: Cardiomyopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…DCM is defined by structural hallmarks of left ventricle dilation and increased left ventricle chamber radius-to-wall thickness ratio, resulting in increased left ventricle wall stress (Dixon and Spinale 2009 HCM is a primary myocardial disease that has variable manifestations because the interactions between the many facets of systolic and diastolic dysfunction of the heart are complex (Lin et al 2002) (Kushwaha et al 1997). …”
Section: Cardiomyopathiesmentioning
confidence: 99%
“…However, significant differences exist with regard to several cardiac characteristics when mice are compared with humans (Table 1) (Gandolfi et al 2011;Dixon et al 2009). An important parameter is heart rate, with an adult mouse heart beating 500-600 times per minute, compared with the 60-100 times typical of the human.…”
Section: Murine Models For Cardiac Diseasementioning
confidence: 99%
“…Swine has also been used in the development of therapies for infarcted patients, such as pharmacological treatments, stem cell transplantation (Min et al 2012, Li et al 2013, and the use of angiogenic growth factors (Dixon & Spinale 2009). Banchi (1904) described the distribution of the coronary artery in humans and some animal species using the artery origin, which is largely responsible for the blood supply to the right posterior heart.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dixon & Spinale (2009), although small animal models such as mice promote the understanding of the cellular and molecular basis of cardiovascular biology, to understand the mechanisms and biological bases of heart failure in humans, it is necessary to use large animals, which exhibit a similar clinical phenotype. Thus, swine have been widely used as a comparative model in recent years due to the anatomical and physiological similarities, both in normal and pathological conditions and in studies on acute heart failure (Santos et al 2012), atherosclerosis (Artinger et al 2009), valvular problems (Maluf et al 1993, Grehan et al 2000 and ventricular function (Hendry 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimize conditions under which CPC can be utilized to maximize their benefit for stem cell transplantation, cardiac progenitor cells need to be tested in large animals [18]. Several studies have been reported in pigs [19] and dogs [10], however, no studies have reported the isolation of cardiac progenitor cells from sheep or their effect on heart repair.…”
Section: Introductionmentioning
confidence: 99%